Arborização urbana como elemento qualificador da ambiência em cidades de porte médio - Carasek, Mirian (2014)
The urban forestry network should be considered an important tool for urban sustainability. The green infrastructure is the important factor for the appreciation and maintenance urban forestry network - squares, parks, green spaces - public and community, which, together with the streets and buildings, helps to compose the urban landscape. This study aims to determine the urban afforestation network as a basic element for the qualification of urban environment in mid-sized cities. The case study, which was conducted in the city of Passo Fundo- RS, aims to contribute to the elaboration of proposals for the qualification of urban environment through factsheets and POE questionnaire (Post Occupancy Evaluation) on user perceptions about the current environment and aspirations with respect to the roads in the city